Implementation of Multicultural Counseling to Reduce Academic Anxiety in Vocational High School Students in Jember - Duwi Sitoresmi; Siti Rochayah; Yuniar Dwi Puspita (Journal of Psychology and Education Counseling (JPEC), 2025)
This study aims to identify the level of academic anxiety among vocational high school (SMK) students prior to receiving intervention, describe the implementation of multicultural counseling, and examine its effectiveness in reducing academic anxiety. The research is grounded in the significant shift in learning culture from junior high school to vocational education, where students are required to adapt to competency-based learning and intensive practical activities. This study employed a case study method with participants selected based on high levels of academic anxiety. Data were collected through observation, in-depth interviews, and documentation, and analyzed qualitatively. The findings indicate that prior to the intervention, students experienced moderate to high levels of academic anxiety, reflected in cognitive, affective, and somatic symptoms. The multicultural counseling process proved effective through the application of cultural understanding, empathic communication, and culturally responsive counseling techniques. The implementation of multicultural counseling combined with the Solution-Focused Brief Counseling (SFBC) approach successfully reduced students' academic anxiety, increased their self-confidence, and enhanced their adaptability to practical learning demands. In conclusion, multicultural counseling is a relevant, responsive, and effective approach for helping SMK students manage academic anxiety arising from their transition to a new learning culture.